The impact of ‘Standing’ on China-U.S. security relations: a constructivist approach to relations between a rising power and an established power - Wang, Pei (2021)
This thesis examines how the concept of ‘standing’, derived from the work of Lebow, impacts China-U.S. security relations. Conventional Realist explanations argue that China’s growing material capacities will likely lead to armed conflict between China, a rising power, and the United States, an established power, based on the structure of the international system and the distribution of power. However, Realist approaches have limitations and deficiencies in explaining China-U.S. security relations. This thesis goes beyond material interests to examine the two powers’ mutual pursuit of ‘standing’ and finds that ‘standing’ has played a major role in China-U.S. security relations. This thesis examines the role played by ‘standing’ in three case studies: the 1995-1996 Taiwan Strait crisis, the U.S. bombing of the Chinese embassy in Belgrade in 1999 and the EP-3 incident in 2001. Drawing on Lebow’s work, this thesis researches and develops the concept of ‘standing’ in the Chinese and U.S. contexts, respectively, using content analysis and semi-structured interviews, with secondary literature as referencing sources. It develops a Constructivist theoretical framework, with ‘standing’ as the key concept, based on the relationship between ‘standing’, ‘identity’ and behaviour, as inferenced by Lebow, while drawing on Hopf and Wendt’s works on identity. The analytical framework is tested in the three cases through process tracing.